2020
DOI: 10.1186/s13722-020-00187-6
|View full text |Cite
|
Sign up to set email alerts
|

A text message intervention for quitting cigarette smoking among young adults experiencing homelessness: study protocol for a pilot randomized controlled trial

Abstract: Background: Cigarette smoking is much more prevalent among young people experiencing homelessness than in the general population of adolescents and young adults. Although many young homeless smokers are motivated to quit, there are no empirically-evaluated smoking cessation programs for this population. It is important that any such program address the factors known to be associated with quitting-related outcomes among homeless young people, to provide ongoing support in a way that accommodates the mobility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The intervention was carried out in a cluster cross-over randomized controlled design such that each drop-in center alternated between serving as an intervention or control site by phase across the field period. After formative work with 26 participants [ 18 ], we settled on a study design that provided a brief group counseling session based on the 5 As (ask, advise, assess, assist, and arrange) [ 19 ] and nicotine patches to all participants, and those in the TMI condition were then sent automated text messages. The study flow is shown in Figure 1 , and a detailed description of the intervention design has been published elsewhere [ 20 ]; here we focus on aspects related to the text messaging component.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention was carried out in a cluster cross-over randomized controlled design such that each drop-in center alternated between serving as an intervention or control site by phase across the field period. After formative work with 26 participants [ 18 ], we settled on a study design that provided a brief group counseling session based on the 5 As (ask, advise, assess, assist, and arrange) [ 19 ] and nicotine patches to all participants, and those in the TMI condition were then sent automated text messages. The study flow is shown in Figure 1 , and a detailed description of the intervention design has been published elsewhere [ 20 ]; here we focus on aspects related to the text messaging component.…”
Section: Methodsmentioning
confidence: 99%
“…Given that TMIs have not been previously implemented for behavior change among young homeless smokers, there is little guidance from the existing literature regarding the frequency and timing of text messages for this population. Therefore, we conducted several focus groups with a total of 18 homeless smokers and elicited usability testing feedback with a separate sample of 10 homeless smokers recruited from the drop-in centers [ 18 ]. During these groups we also reviewed the content of texts with participants and made sure that receiving texts would be feasible for this population to inform decisions about the optimal content (eg, what types of messages would likely be most effective in dealing with cravings) and wording (eg, how to word the text message so that it motivates homeless youth to stay quit).…”
Section: Methodsmentioning
confidence: 99%
“…The intervention was carried out in a cluster cross-over randomized controlled design such that each drop-in center alternated between serving as an intervention or control site by phase across the field period. After formative work with 26 participants [18], we settled on a study design that provided a brief group counseling session based on the 5 As (ask, advise, assess, assist, and arrange) [19] and nicotine patches to all participants, and those in the TMI condition were then sent automated text messages. The study flow is shown in Figure 1, and a detailed description of the intervention design has been published elsewhere [20]; here we focus on aspects related to the text messaging component.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The project team generated 174 text messages to send to all TMI participants (see previous work [20] for example texts by the 5 main foci of the TMI program as well as TMI time point [ie, pre-quit day texts, quit day texts, early post-quit texts, later post-quit texts]). Text message content was informed by our prior work with homeless smokers to identify key factors associated with motivation to quit, consultation with the text messaging literature, and review of text messages included in other public domain smoking cessation programs (eg, Text2Quit [21] and SmokefreeTXT [22]).…”
Section: Description Of Tmimentioning
confidence: 99%
“…Furthermore, how adolescents and young adults experience smoking cessation makes it crucial to understand how the smoking cessation process affects their lives. Given the early stages of smoking cessation interventions geared towards young people, studies suggest that young people are more likely to prefer to take on the smoking cessation process without seeking the support of health professionals or cessation programs [15]. Therefore, an understanding of the lived experiences and coping mechanisms of such young people who become successful in their solitary cessation journey can serve as useful information for health promotion interventions towards new strategies for smoking cessation programs.…”
Section: Introductionmentioning
confidence: 99%